2017
DOI: 10.1186/s12889-017-4121-2
|View full text |Cite
|
Sign up to set email alerts
|

User-experiences with a web-based self-help intervention for partners of cancer patients based on acceptance and commitment therapy and self-compassion: a qualitative study

Abstract: BackgroundPartners of cancer patients are the cornerstone of supportive cancer care. They assume different roles and responsibilities that optimally support the patient. Such support is highly demanding, and many partners report (mental) health problems. However, many of them do not use professional supportive care themselves. Offering a Web-based self-help intervention based on Acceptance and Commitment Therapy (ACT) and self-compassion could be an important resource to support this group. This qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 49 publications
2
50
0
3
Order By: Relevance
“…The majority of the caregivers mentioned that they were not in need of peer contact or they thought talking to others in a more advanced stage would be too confronting. These results are in line with the results in previous studies, which concluded that the fear of negative prospects can prevent participants from seeking peer contact [35, 36]. Although peer support can have advantages, having contact with others who are coping well can provide hope and generate information which positively impacts upon one’s own problem solving skills [36, 37].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of the caregivers mentioned that they were not in need of peer contact or they thought talking to others in a more advanced stage would be too confronting. These results are in line with the results in previous studies, which concluded that the fear of negative prospects can prevent participants from seeking peer contact [35, 36]. Although peer support can have advantages, having contact with others who are coping well can provide hope and generate information which positively impacts upon one’s own problem solving skills [36, 37].…”
Section: Discussionsupporting
confidence: 90%
“…ACT incorporates mindfulness-and acceptance-based processes to reduce interference of difficult internal experiences (e.g., fear, depressive symptoms) with meaningful activities and QoL that has been used in partners of cancer patients [47]. ACT can help partners clarify and commit to their personal values and be more self-compassionate when experiencing negative thoughts and feelings [48]. Because a large portion of partners in this study reported QoL deficits, this may be an especially beneficial approach to alleviate factors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The content of the support program for informal caregivers is based on an online intervention aimed at partners of patients with cancer [ 37 , 38 ]. This intervention, based on ACT, was adapted to the specific needs of ALS caregivers.…”
Section: Methodsmentioning
confidence: 99%